PENGARUH PENGGUNAAN MINDMAPPING TERHADAP KEMAMPUAN MENGINGAT MATERI IPA SISWA KELAS VI SD - Adel Adel; Rizky Juanda; Farid Padilah; M Iqbal Arrosyad (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research was carried out in response to the low retention ability of students in learning science, which highlights the urgency for a more engaging and effective instructional strategy. The primary purpose of this study was to examine the influence of the mind mapping technique on sixth-grade students’ memory of science concepts. A quantitative method with a pre-experimental design was implemented, involving 28 sixth-grade learners from Muhammadiyah Elementary School Pangkalpinang as the sample. Conducted in October 2025, the procedure consisted of administering a pre-test to assess students’ baseline memory performance, applying mind mapping during the learning sessions, and administering a post-test to evaluate learning improvement after the treatment. Data were gathered using a written assessment, and both descriptive and inferential statistical analyses were employed to compare students’ scores before and after the intervention. The results demonstrated noticeable progress in the experimental group exposed to project-based instruction, where the mean score increased from 75.71 to 88.57. In contrast, the control group taught through conventional methods also experienced an improvement from 62.85 to 81.42. The N-Gain analysis yielded values of 0.46 for the experimental group and 0.45 for the control group, both categorized as moderate, although the enhancement in the experimental group appeared more consistent and substantial. Moreover, the independent sample t-test produced a significance value of 0.000 (< 0.05), indicating a statistically significant difference in learning outcomes between the two groups following the intervention.